BIRC3 single nucleotide polymorphism associate with asthma susceptibility and the abundance of eosinophils and neutrophils. (7th February 2017) - Roscioli, Eugene; Hamon, Rhys; Ruffin, Richard E.; Grant, Janet; Hodge, Sandra; Zalewski, Peter; Lester, Susan
Abstract: Background and objective : Aberrant apoptosis is a disease susceptibility mechanism relevant for asthma, whereby fragility of the airway epithelium and enhanced survival of inflammatory cells, contributes to its pathogenesis and prolongation. Cellular Inhibitor of Apoptosis Proteins (cIAP) suppress apoptosis, and participate in the immune response. In this study, single nucleotide polymorphisms (SNP) in the BIRC2 (codes cIAP1) and BIRC3 (cIAP2) genes were evaluated for an association with asthma. Methods : Caucasian asthmatic ( n = 203) and control ( n = 198) subjects were selected from participants in the North West Adelaide Health Study. SNPs ( n = 9) spanning the consecutively positioned BIRC2 and BIRC3 genes, were selected using a haplotype tagging approach. Alleles and haplotype associations were analysed by logistic regression, assuming an additive genetic model, and adjusted for gender and atopy. Results : The frequency of the minor allele for the BIRC3 SNP rs3460 was significantly lower in asthmatics compared to the control cases ( P = 0.046). BIRC3 SNPs rs7928663 and rs7127583 associated with a reduction in eosinophil and neutrophil abundance when assessed across the study population (multivariate P values = 0.002, and 0.005, respectively). Further, the frequency of a haplotype tagged by rs3460, rs7928663 and rs7127583 was reduced in the asthma sub group ( P = 0.05), while the presence of the major allele for rs7928663 associated with an increased load of circulating eosinophils and neutrophils (multivariate P value = 0.001). Conclusions : Polymorphisms in the BIRC3 gene, but not BIRC2, are associated with a protective effect with regards to asthma susceptibility, and a reduced load of inflammatory cells.